Development of intermediate scale structure near the peak of the F region within an equatorial plasma bubble. Issue 4 (2nd April 2014) - Bhattacharyya, A.; Kakad, B.; Sripathi, S.; Jeeva, K.; Nair, K. U.
Abstract Scintillation observations are used to study the evolution of intermediate scale (~100 m–few kilometers) irregularities through growth of the Rayleigh‐Taylor (R‐T) instability on the bottom side of the post‐sunset equatorial F region during magnetically quiet periods. Amplitude scintillations on a VHF signal from a geostationary satellite, recorded by spaced receivers at an equatorial station, are used to compute as a function of local time: (1) the coherence scale length for spatial variations of intensity in the ground scintillation pattern, which is linked with the spectrum of the intermediate scale irregularities near the peak of the equatorial F region that contribute the most to the observed scintillations; and (2) the "random velocity", which accounts for the de‐correlation of the spaced receiver signals. The relationship between the coherence scale length and the random velocity for saturated scintillations at different local times suggests that (1) the random velocity is linked with fluctuations in the drift velocity of the irregularities caused by the perturbation electric fields associated with the R‐T instability rather than structural changes in the intermediate scale irregularities, (2) the spectrum of intermediate scale irregularities in the equatorial F peak region tends to be shallowest after the decay of the perturbation electric fields associated with the R‐T instability, and (3) evolution of intermediate‐scale irregularity spectrum in the equatorial plasma bubble near the equatorial F region peak depends on season and solar flux. These have implications for observation of low‐latitude L‐band scintillations.